Simplify the expression by combining like terms.
7x-3+2x+6
A
12x
B
5x + 9
C
9x + 3
D
9x - 3
15 answers
The simplified expression is 9x + 3.
Simplify by using the distributive property.
-3(2x - 4)
A
6x
B
-6x - 4
C
6x + 12
D
-6x + 12
-3(2x - 4)
A
6x
B
-6x - 4
C
6x + 12
D
-6x + 12
The simplified expression using the distributive property is -6x + 12.
Solve using inverse operations.
-3/5x = 2/5
A
−15-\frac{1}{5}−
5
1
B
23\frac{2}{3}
3
2
C
−625-\frac{6}{25}−
25
6
D
−23-\frac{2}{3}−
3
2
-3/5x = 2/5
A
−15-\frac{1}{5}−
5
1
B
23\frac{2}{3}
3
2
C
−625-\frac{6}{25}−
25
6
D
−23-\frac{2}{3}−
3
2
To solve for x, we can use inverse operations to isolate x by getting rid of the fraction.
First, we can multiply both sides of the equation by the reciprocal of -3/5, which is -5/3, to cancel out the fraction on the left side:
x = (2/5) * (-5/3)
Simplifying, we get:
x = -10/15
x = -2/3
The correct option is:
D) -23 - 2/3 - 3/2
First, we can multiply both sides of the equation by the reciprocal of -3/5, which is -5/3, to cancel out the fraction on the left side:
x = (2/5) * (-5/3)
Simplifying, we get:
x = -10/15
x = -2/3
The correct option is:
D) -23 - 2/3 - 3/2
Choose the best equation that fits the word problem below.
Sarah is planning to buy some books. Each book (b) costs $15. How many books can Sarah purchase if she has saved $60?
A
15 + 60 = b
B
15 + b = 60
C
60b = 15
D
15b = 60
Sarah is planning to buy some books. Each book (b) costs $15. How many books can Sarah purchase if she has saved $60?
A
15 + 60 = b
B
15 + b = 60
C
60b = 15
D
15b = 60
The best equation that fits the word problem is:
B) 15 + b = 60
This equation represents the fact that the total cost (15b) plus the $15 Sarah has saved must equal $60, in order for her to be able to purchase the books.
B) 15 + b = 60
This equation represents the fact that the total cost (15b) plus the $15 Sarah has saved must equal $60, in order for her to be able to purchase the books.
Spencer prepaid a 12-month membership to Power Score Gym. He recieved a one-time discount of $35 for prepaying. Spencer paid a total of $205.
Which equation can Spencer use to find m, the regular cost per month?
A
12m - 35 = 205
B
35(m - 12) = 205
C
12(m - 35) = 205
D
35m - 12 = 205
Which equation can Spencer use to find m, the regular cost per month?
A
12m - 35 = 205
B
35(m - 12) = 205
C
12(m - 35) = 205
D
35m - 12 = 205
The equation that Spencer can use to find m, the regular cost per month, is:
A) 12m - 35 = 205
This equation represents the fact that the cost of 12 months (12m) minus the one-time discount ($35) is equal to the total amount Spencer paid ($205).
A) 12m - 35 = 205
This equation represents the fact that the cost of 12 months (12m) minus the one-time discount ($35) is equal to the total amount Spencer paid ($205).
Solve the equation and show all steps:
5x-7=3
5x-7=3
To solve the equation 5x - 7 = 3, we need to isolate the variable x.
First, we can add 7 to both sides of the equation to get rid of the constant term on the left side:
5x - 7 + 7 = 3 + 7
Simplifying, we have:
5x = 10
Next, we divide both sides of the equation by 5 to solve for x:
(5x)/5 = 10/5
Simplifying further, we get:
x = 2
So the solution to the equation is x = 2.
First, we can add 7 to both sides of the equation to get rid of the constant term on the left side:
5x - 7 + 7 = 3 + 7
Simplifying, we have:
5x = 10
Next, we divide both sides of the equation by 5 to solve for x:
(5x)/5 = 10/5
Simplifying further, we get:
x = 2
So the solution to the equation is x = 2.
Solve the equation, show all steps:
y/2 + 22 = 28
y/2 + 22 = 28
To solve the equation (y/2) + 22 = 28, we need to isolate the variable y.
First, we can subtract 22 from both sides of the equation to get rid of the constant term on the right side:
(y/2) + 22 - 22 = 28 - 22
Simplifying, we have:
(y/2) = 6
Next, we can multiply both sides of the equation by 2 to solve for y:
(2)*(y/2) = 6*(2)
Simplifying further, we get:
y = 12
So the solution to the equation is y = 12.
First, we can subtract 22 from both sides of the equation to get rid of the constant term on the right side:
(y/2) + 22 - 22 = 28 - 22
Simplifying, we have:
(y/2) = 6
Next, we can multiply both sides of the equation by 2 to solve for y:
(2)*(y/2) = 6*(2)
Simplifying further, we get:
y = 12
So the solution to the equation is y = 12.
Solve the equation and show all steps:
2/3n - 6 = -8
2/3n - 6 = -8
To solve the equation (2/3)n - 6 = -8, we need to isolate the variable n.
First, we can add 6 to both sides of the equation to get rid of the constant term on the left side:
(2/3)n - 6 + 6 = -8 + 6
Simplifying, we have:
(2/3)n = -2
Next, we can multiply both sides of the equation by the reciprocal of 2/3, which is 3/2, to solve for n:
(3/2)(2/3)n = -2(3/2)
Simplifying further, we get:
(1)n = -3
n = -3
So the solution to the equation is n = -3.
First, we can add 6 to both sides of the equation to get rid of the constant term on the left side:
(2/3)n - 6 + 6 = -8 + 6
Simplifying, we have:
(2/3)n = -2
Next, we can multiply both sides of the equation by the reciprocal of 2/3, which is 3/2, to solve for n:
(3/2)(2/3)n = -2(3/2)
Simplifying further, we get:
(1)n = -3
n = -3
So the solution to the equation is n = -3.